The difference of surface coarseness of high-copper amalgam restoration material before and after 38% hydrogen peroxide application by in vitro in-office bleaching technique - Gustina, Nurmala; Natasasmita, Setiawan; Aripin, Dudi (Universitas Padjadjaran, 2007)
Hydrogen peroxide is an effective agent to take off tooth colouring. This bleaching agent can cause microstructural change on amalgam restoration surfaces. The aim of this research is to know the difference of surface roughness of high-copper amalgam restoration materials before and after 38% hydrogen peroxide application by in-office bleaching technique. The sample was used consist of ten specimens of high-copper amalgam restorations which was applied by hydrogen peroxide 38%. The surface roughness was measured by the surface tester (Surtronic 3P). The result of this research was reached by t-test paired calculation is the differences of surface roughness of amalgam restorations before and after first 15 minutes either second 15 minutes hydrogen peroxide 38% application didn’t show significant differences. The conclusion of this research is no statistically significant difference of surface roughness of high-copper amalgam restoration materials before and after 38% hydrogen peroxide application by in-office bleaching technique.